Enhancing Federal Government Mandates to Ensure Continuity of Heritage Legacies - Aziz, Sarah; Hasan, Siti Zuhaili (Kajian Malaysia : Journal of Malaysian studies, 2017)
The responsibility to ensure a legacy is continued, particularly for cultural and natural heritage, often rests with the government agencies, who are armed with the necessary legislative mandates to safeguard and protect them. Heritage in itself has a complex meaning, from the determination of the subject matter itself, the characterisation of its nature and value, to regulating the interactions that may have positive or negative impacts to it. It transcends guarding an object or subject, and involves the complex human-environment relations to the object or subject, encompassing that which is tangible and intangible. In addition, there are times when both cultural and natural heritage become interlinked resulting in it being categorised as mixed heritage, which requires a different set of approaches that complements the need for both cultural and natural heritage conservation. The question to be addressed revolves on what needs to be safeguarded and how can it be properly contextualised, taking into account the complex nature of heritage conservation and the interactions between those who know, those who have "inherited" and have cared for it, with those who are tasked to safeguard it. In addition, there is a need to look at the roles of those who act as custodians, by exploring what entails from the mandate given, towards enabling a collaborative arrangement, in order to ensure that existing mandates become complementary and mutually supportive. This article looks at the intricate relationship focusing on different Federal government mandate holders of cultural and natural heritage conservation, taking into account the federated system of government in place in Malaysia. It briefly discusses a segment of the current Federal government arrangement, and challenges as well the opportunities ahead in Malaysia.